Evolution and thematic structure of research on the right to a healthy environment in Scopus (2018–2023) - Polania, Libardo Ramón; Castillo, Verenice Sánchez (Journal of Ecohumanism, 2024)
This article analyzed scientific output indexed in Scopus regarding the right to a healthy environment during the 2018–2023 period, with the aim of identifying its evolution, its disciplinary configuration, and its main lines of research. A descriptive, retrospective, and longitudinal bibliometric study was conducted based on an advanced search across titles, abstracts, and keywords, which retrieved 713 documents. The analysis encompassed seven indicators: total publications, citation distribution, disciplinary fields, primary sources, document types, keywords, and lines of research. The findings revealed sustained growth in scholarly output, with a higher concentration occurring in the final years of the period. The disciplinary structure was concentrated primarily within the social sciences, followed by environmental sciences, thereby demonstrating an inherently interdisciplinary field characterized by a distinct legal and political-institutional foundation. In terms of publication formats, journal articles predominated, although book chapters also held a significant position. A keyword co-occurrence network analysis identified five thematic clusters: human rights and environmental rights; climate change and litigation; environmental protection and regulation; sustainability and impacts; and environmental justice with democratic participation. Taken together, the study demonstrated that the right to a healthy environment has established itself as an expanding scientific agenda, increasingly linked to issues of enforceability, climate justice, and environmental governance.